Professional Investor Relations within the Firm - Kirk, Marcus P.; Vincent, James D. (The Accounting Review, 2014)
ABSTRACT: This paper investigates the effect of investments in internal investor relations (IR) departments on firm outcomes. We find that companies initiating internal professional IR experience increases in disclosure, analyst following, institutional investor ownership, liquidity, and market valuation relative to a matched sample of control firms. We also examine the differential impact the exogenous shock of Regulation Fair Disclosure (Reg FD) had on firms with an established professional IR department. We find these IR firms more than doubled their level of public disclosure post-Reg FD. Despite IR firms losing a potential communications channel following Reg FD adoption, we find they did not suffer adversely and instead show a post-Reg FD increase in analyst following, institutional investors, and liquidity relative to a control sample of similar non-IR firms. This implies that the effectiveness of professionalized internal IR increased post-Reg FD consistent with IR firms being relatively better positioned to navigate the more complicated regulatory environment. JEL Classifications: D82; M41; G11; G12; G14; G24 Data Availability: Data are publicly available from the sources identified in the paper with the exception of the membership data from the National Investor Relations Institute, which is a proprietary dataset.